2020
DOI: 10.5152/ejbh.2020.5188
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Self-Efficacy, Body Image and Sexual Adjustment of Women with Breast Cancer

Abstract: European Journal of Breast Health (Eur J Breast Health) is an international, scientific, open access periodical published by independent, unbiased, and double-blinded peer-review principles. It is the official publication of the Turkish Federation of Breast Diseases Societies, and Senologic International Society is the official supporter of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This finding was consistent with Brunet and his colleagues (2022) study, which showed that partner support plays a very important role in adapting to the body image altered in women with BC (17). The results of Arikan et al's study showed that women who did not have the support of their husbands had a lower body image (18). Spouse emotional support improves women's self-esteem and psychological status (19), and involvement in childcare helps to offset maternal and housekeeping roles (20).…”
Section: Discussionsupporting
confidence: 87%
“…This finding was consistent with Brunet and his colleagues (2022) study, which showed that partner support plays a very important role in adapting to the body image altered in women with BC (17). The results of Arikan et al's study showed that women who did not have the support of their husbands had a lower body image (18). Spouse emotional support improves women's self-esteem and psychological status (19), and involvement in childcare helps to offset maternal and housekeeping roles (20).…”
Section: Discussionsupporting
confidence: 87%
“…When duplicate articles from the same institution were reported, either the better quality or most recent publication was included. We extracted data and recorded the information: (1) the rst author, the year of publication, and the country; (2) study type; (3) study setting; (4) sample size; (5) sample characteristic; (6) intervention type, components, dosage and mode; (7) facilitators; (8) outcome measures; (9) duration of follow-up, and (10) results. Meanwhile, We extracted data for calculating the effect size.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…Receiving these treatments is associated with negative body image, such as breast loss, hair loss, skin damage, and more. These changes and losses in appearance can lead to cognitive, behavioral, and emotional changes, and a perceived loss of femininity and attractiveness, which can affect their self-esteem and quality of life [2][3][4][5], and also it will negatively affect the well-being of couples and lead to sexual disorders [6,7]. Therefore, there is a need to provide support for the appearance-related side effects of treatment to maintain their psychosocial well-being.…”
Section: Introductionmentioning
confidence: 99%
“…This problem must be resolved immediately because it can worsen the body image of survivors because sexuality is often juxtaposed with body image in establishing a woman's identity. Women must be empowered and their self-efficacy in self-care must be improved so that they have positive coping (Arıkan et al, 2020). Fatigue Management Interventions carried out in the form of calm yoga are able to provide the effect of harmony, calmness, mood changes and body image improvement if done in a structured and consistent manner.…”
Section: The Effect Of Gpa On Body Imagementioning
confidence: 99%